Islam and the Economic Challenge - Imtiaz Uddin Ahmad (International Institute of Islamic Thought, 1992)
I consider the task of reviewing this book an honor as well as a challenge. My task is made even more difficult and the challenge moE significant when I read excellent reviews from both intellectual spectra, Western as well as Islamic. From the West, Kenneth Boulding, an eminent behavioral scientist and social economist, expresses his admiration both for the author’s readable style as well as the depth and the maturity of his knowledge when he writes: This is an excellent work . . . His understanding is quite sophisticated. At the same time his style is clear and he writes with humanity and a very deep concern for the welfare of the human race. From the East, the book has already received and incorporated comments and suggestions from a number of economists at the forefront of research in Islamic economics, among them Dr. Nejatullah Siddiqui and Professor Khurshid Ahmad. The latter economist has very succinctly summarized not only his own views but also thm of other Islamic scholars when, in the foreword, he writes: Dr. Chapra has dealt with the subject as a trained social scientist and objective Islamic scholar. His grasp of the contemporary systems and their problems is thorough and incisive, his presentation of Islamic economic order is concise and convincing. His balanced critique of the western systems as well as that of the contemporary Islamic society is presented in a style that is scholarly yet simple, clear and prescriptive. . . . Dr. Chapra has clearly demonstrated that well being can not be attained through the pursuit of material possessions alone and that efficiency and equity can become operational concepts only if they are redefined in the context of their linkage to moral values and socioeconomic structures.”